Ethical Challenges in Pandemics. Introduction - Schmidhuber, Martina; Reis, Andreas; Frewer, Andreas (Pandemics and Ethics. Development – Problems – Solutions, 2023)
The corona crisis causes many uncertainties in addition to health concerns and fears: far-reaching restrictions in the private sector, existential fears that arise for many due to the economic situation—both for private individuals and for (smaller and larger) entrepreneurs –, lack of personal contacts, young people who wonder whether they will find work after their vocational training. And one open question that nobody can answer: When will life finally be “like before”? This shows how vulnerable human beings are Of course, some are more affected than others. Here a gap opens up between those who were socio-economically better and worse off before the pandemic. Social inequalities that already existed became even more apparent during the pandemic. For those who had to fight the everyday challenges of life before the pandemic—single parents, people in precarious employment, people with a migrant background or pre-existing conditions etc.—the situation worsened. Nevertheless, the pandemic seems to affect everyone in some way and to make everyone aware of their vulnerability.
CRIS-Team Scopus Importer:2024-06-28